Employee Output, Absenteeism, and Turnover A Case Study in Mechanical Corporation - Desva Wahyuni; Ramon Zamora; Lukmanul Hakim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The impact of disagreement on productivity, absenteeism, and employee turnover were investigated in this study. Quantitative methods were employed in this descriptive survey investigation. Research participants were chosen at random from a stratified population. We utilised IBM SPSS version 22 to generate the results for discussion, and the instrument was a questionnaire. Employee performance is negatively affected by disagreement, which leads to frequent absence, low production, and turnover, according to the study. Conflicts in the workplace have a substantial impact on productivity, absenteeism, and attrition, which has important leadership implications. Understanding and resolving the unique conflicts that each individual encounters is essential. Organisational leaders should ensure that positions are designed suitably for people to avoid duplication of effort and promote harmonious collaboration. They can use this to strengthen their bonds with coworkers. Organisational conflicts arising from relationships, tasks, and interpersonal dynamics will decrease as a result. Conflict and its negative effects on both employees and the company can be lessened in this way as well. There doesn't seem to be any literature on the topic of conflict at Ghanaian universities. In contrast to previous research, this one uses mechanical Corporation in Palembang as a case study to analyse the correlation between conflict and performance metrics including productivity, absenteeism, and turnover.